Stephan E. C. Wendehorst: British Jewry, Zionism and the Jewish State 1936–1956 - Shindler, Colin (Medaon, 2014)
Stephan E. C. Wendehorst: British Jewry, Zionism and the Jewish State 1936-1956, New York: Oxford University Press, 2012, 422 p., ISBN 9780199265305, USD 110,00. Reviewed by Colin Shindler.